Microplastics in corals: an emergent threat - Soares, Marcelo de Oliveira (2021)
This article seeks to present a summary of knowledge and thus improve awareness of microplastic impacts on corals. Recent research suggests that microplastics have a variety of species-specific impacts. Among them, a reduced growth, a substantial decrease of detoxifying and immunity enzymes, an increase in antioxidant enzyme activity, high production of mucus, reduction of fitness, and negative effects on coral-Symbiodiniaceae relationships have been highlighted in recent papers. In addition to this, tissue necrosis, lower fertilization success, alteration of metabolite profiles, energetic costs, decreased skeletal growth and calcification, and coral bleaching have been observed under significant concentrations of microplastics. Furthermore, impairment of feeding performance and food intake, changes in photosynthetic performance and increased exposure to contaminants, pathogens and other harmful compounds have also been found. In conclusion, microplastics may cause a plethora of impacts on corals in shallow, mesophotic, and deep-sea zones at different latitudes; underlining an emerging threat globally.